2014
DOI: 10.1177/1545968314526306
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Visual Scanning Exercises Integrated Into Physiotherapy in Patients With Unilateral Spatial Neglect Poststroke

Abstract: Intensive saccadic eye movement training with VSE integrated with task-specific activities has a significant effect on USN in patients poststroke. Results of this study are supported by findings from previously reviewed literature in the sense that the effect of saccadic eye movement training with VSE as an intervention approach has a significant effect on the visual perceptual processing of participants with USN poststroke. The significant improved visual perceptual processing translate to significantly bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…These authors reported the geometric mean and 95% confidence interval (CI) at baseline and the end of each week of the treatment period. The expected geometric mean of the Barthel Index value at onset was 45 ( 12 ) and an improvement in the change from baseline at 2 weeks for the combination of VSE integrated with task-specific activities group (experimental group) compared with the task-specific activities group (control group) is 36 which is 0.214 on the logarithmic (base 10) scale. From the reported 95% CI for the geometric mean, a SD of 0.179 on the log scale was calculated.…”
Section: Methods and Analysismentioning
confidence: 97%
See 3 more Smart Citations
“…These authors reported the geometric mean and 95% confidence interval (CI) at baseline and the end of each week of the treatment period. The expected geometric mean of the Barthel Index value at onset was 45 ( 12 ) and an improvement in the change from baseline at 2 weeks for the combination of VSE integrated with task-specific activities group (experimental group) compared with the task-specific activities group (control group) is 36 which is 0.214 on the logarithmic (base 10) scale. From the reported 95% CI for the geometric mean, a SD of 0.179 on the log scale was calculated.…”
Section: Methods and Analysismentioning
confidence: 97%
“…Recruitment and assessment of patients will be done in each of the rehabilitation centers in a consecutive sequence based on the number of patients in a particular center at a given time until an adequate and representative sample group ( n = 100) for the trial has been reached. An adequate and representative sample size required for phase 1 of the study was calculated based on a relatively small, but similar study ( 12 ). These authors reported the geometric mean and 95% confidence interval (CI) at baseline and the end of each week of the treatment period.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with spatial neglect, spontaneous saccadic eye movements or head movements are restricted to the ipsilesional visual hemifield and may rarely cross midline (Zoltan, 1996 ; Chaikin, 2007 ). Visual scanning training expands these movements into the contralesional space by repeatedly using cues, such as “point your right (unimpaired) hand to the left side” or “look to the left.” Recent studies have shown that visual scanning exercises increase perceptual processing (Where networks) in neglect patients, thereby leading to better visual function and ability to perform activities of daily living (van Wyk et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%